PERFORMANCE OF SOFTWARE IMAGE COMPRESSION - Priono, Budi (Jurnal Ilmiah Teknologi dan Rekayasa, 2016)
This research is comparison among the data processing software, as seen from the results of PSNR.  There are 3 different image file types (homogeneous, heterogeneous, and semi-heterogeneous) and 5 pieces of data processing software. Each software creates as many as 50 files of processed data, and grouped according with the type of the image. Any results that are grouped will be calculated the value of PSNR and compared. A homogeneous image the software that has the best performance is Adobe Photoshop, the calculation of the value of PSNR Compression and PSNR decompression. A heterogeneous image the software that has the best performance remained Adobe Photoshop, because it has a value of average PSNR highest and decompress. A Semi heterogeneous image the software that has the best performance is Adobe Photoshop, the calculation of the value of PSNR Compression and PSNR decompression. So that Adobe Photoshop has the best compression quality. Keywords: JPG and BMP Format, Image, Performance, Software, Compression.